Detrimental effects of intense vasodilation in women with acute heart failure: novel insights from a prospective randomized controlled trial. (3rd October 2022) - Wussler, D; Belkin, M; Walter, J; Kozhuharov, N; Goudev, A; Flores, D; Maeder, M; Shrestha, S; Gualandro, D; De Oliveira, M; Rickli, H; Breidthardt, T; et al.
Abstract: Background: Guidelines recommend evaluating the risk/benefit ratio of novel therapies individually in women and men, as the pathophysiology and the response to treatment may differ according to sex. Among patients with acute heart failure (AHF), a strategy of intensive vasodilation, compared with usual care, overall did provide comparable outcomes. However, sex-specific differences in heart failure pathophysiology and the effect of the strategy in women with AHF remained unclear. Purpose: To characterize sex-specific differences in heart failure pathophysiology and to evaluate the effect of a strategy that emphasized early intensive and sustained vasodilation in women with AHF. Methods: In a randomized, open-label blinded-end-point trial patients hospitalized for AHF were enrolled in 10 hospitals in Switzerland, Bulgaria, Germany, Brazil, and Spain. Inclusion criteria were AHF expressed by acute dyspnea and increased plasma concentrations of natriuretic peptides, systolic blood pressure ≥100 mmHg, and a plan for treatment in a general ward. Patients were randomized 1:1 to a strategy of early intensive and sustained vasodilation throughout the hospitalization or usual care. The primary end point was a composite of all-cause mortality or rehospitalization for AHF at 180 days. The subgroup analysis according to sex was predefined. Results: Among 781 patients who completed the trial, 288 (36.9%) were women. Women were significantly older, had a higher systolic blood pressure at presentation and a more common history of diastolic dysfunction (all ps<0.05), whereas men had a significantly higher body surface area, a more common history of ischemic heart disease and a significant lower left ventricular ejection fraction (all ps<0.05). The primary end point, a composite of all-cause mortality or rehospitalization for AHF at 180 days, occurred in 53 female patients (37.9%) in the intervention group (including 28 deaths [20.0%]) and in 35 female patients (23.6%) in the usual care group (including 22 deaths [14.9%]) (absolute difference for the primary end point, 14.3%; adjusted hazard ratio, 1.62 [95% CI, 1.05–2.50]; P=0.03). Conclusion: Among women with AHF, a strategy of early intensive and sustained vasodilation, compared with usual care, had a detrimental effect on a composite outcome of all-cause mortality and AHF rehospitalization at 180 days. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): University Hospital Basel